Transrectal rigid-hybrid NOTES cholecystectomy can be performed without peritoneal contamination: a controlled porcine survival study - Müller, Philip C.; Senft, Jonas; Gath, Philip; Steinemann, Daniel; Nickel, Felix; Billeter, Adrian; Müller, Beat P.; Linke, Georg R. (Surgical endoscopy and other interventional techniques, 2018)
Background and study aims: The risk of infectious complications due to peritoneal contamination is a major concern and inhibits the widespread use of transrectal NOTES. A standardized rectal washout with a reversible colon occlusion device in situ has previously shown potential in reducing peritoneal contamination. The aim of this study was to compare the peritoneal contamination rate and inflammatory reaction for transrectal cholecystectomy after ideal rectal preparation (trCCE) and standard laparoscopic cholecystectomy (lapCCE) in a porcine survival experiment. Methods: Twenty pigs were randomized to trCCE (n = 10) or lapCCE (n = 10). Before trCCE, rectal washout was performed with saline solution. A colon occlusion device was then inserted and a second washout with povidone-iodine was performed. The perioperative course and the inflammatory reaction (leukocytes, C-reactive protein) were compared. At necropsy, 14 days after surgery the abdominal cavity was screened for infectious complications and peritoneal swabs were obtained for comparison of peritoneal contamination. Results: Peritoneal contamination was lower after trCCE than after lapCCE (0/10 vs. 6/10; p = 0.003). No infectious complications were found at necropsy in either group and postoperative complications did not differ (p = 1.0). Immediately after the procedure, leukocytes were higher after lapCCE (17.0 ± 2.7 vs. 14.6 ± 2.3; p = 0.047). Leukocytes and C-reactive protein showed no difference in the further postoperative course. Intraoperative complications and total operation time (trCCE 114 ± 32 vs. 111 ± 27 min; p = 0.921) did not differ, but wound closure took longer for trCCE (31.5 ± 19 vs. 13 ± 5 min; p = 0.002). Conclusions: After standardized rectal washout with a colon occlusion device in situ, trCCE was associated without peritoneal contamination and without access-related infectious complications. Based on the findings of this study, a randomized controlled clinical study comparing clinical outcomes of trCCE with lapCCE should be conducted.